The comparison of physiological profile between elite and beginner badminton male players / Muhammad Fariz Ismail - Ismail, Muhammad Fariz (2014)
There are absence of spellbinding information on the physiological and physical profiles in the elite and beginner badminton male players in Pahang, Malaysia. The purpose behind this study is to gauge and compare the body composition, aerobic fitness, muscular strength and power, flexibility, speed and agility of the elite and beginner badminton male players in Pahang, Malaysia. Twenty-five elite male players who included in this study was a member of the Pahang Badminton Squad in 2014 and thirty beginner male players was a member of Badminton Amateur Academy of Pahang volunteered for this study. Before start the field tests, the anthropometric measurement of players like height, weight and arm span has been taken. There were five field tests carried out to players which was 20m multistage shuttle-run, vertical jump, sit and reach, 5, 10, 20m speed and 505 agility test. The tests were carried out over two days, distributed into two sessions, allowing a day rest period between each days. Based on the study, we found that for aerobic fitness, elite (13 .45±1.10) was better than beginner (9.52±1.46). For muscular characteristics, elite (58.20±4.03) was better than beginner (49.13±6.03). For flexibility, elite (20.16±3.82) was quite similar to beginner (18.27±4.08). For speed, elite (3.48±0.30) was faster than beginner (3.72±0.23). Lastly for agility, elite (2.50±0.22) was quick than beginner (2.72±0.22). Taking everything into account, this study demonstrates that the elite badminton players are taller, lighter and stronger (in outright terms) look at to the beginner badminton players. From these results, we can conclude that badminton is a fast movement sport that needs a blend combination of fine technical skills and high contains of physiological fitness.